Environmental Risk Information Seeking: The Differential Roles of Anxiety and Hopelessness. Issue 7 (3rd October 2019) - Hmielowski, Jay D.; Donaway, Rebecca; Wang, Meredith Y.
ABSTRACT: Americans' concern about water quality has increased over the years. Indeed, several water issues made national news coverage during the past few years, such as lead in Flint, Michigan, algae blooms in Florida, and water quality at the Rio Olympics. In this study, we test two alternate paths of engagement relative to how people respond to water problems. First, we examine anxiety as a key variable that triggers active information seeking behaviors. Second, we look at hopelessness as an intervening variable that could explain why some people become disengaged with issues. Additionally, we test whether response efficacy moderates the relationships between perceiving a problem with water and these emotions. Using survey data collected during the fall of 2015, we examine the role of different emotions in increasing and decreasing active information seeking behaviors.